Less statin associated adverse events after initiation of pitavastatin compared with atorvastatin and rosuvastatin. (14th October 2021) - Lin, J L; Chen, P S; Li, Y H
Abstract: Background: Statin associated adverse events (SAAEs), including hepatitis, myopathy and new onset diabetes mellitus (NODM), are major reasons that prevent the use of statins. We compared the risk of SAAEs among the commonly used statins to see if SAAEs were similar among the statins. Methods: We retrieved data from the Taiwan National Health Insurance Research Database. From January 2013 to December 2017, all statin-treated patients without diabetes at baseline were enrolled. We classified eligible patients into pitavastatin (2–4mg/day), moderate-intensity statin (MIS [atorvastatin 10–20 mg/day or rosuvastatin 5–10 mg/day]), and high-intensity statin group (HIS [atorvastatin ≥40 mg/day and rosuvastatin ≥20mg/day]). The study endpoint is a composite of safety events, including hepatitis, myopathy, and NODM. All patients were followed-up for at least one year until December 2018. We used propensity score to balance the baseline differences between the 3 statin groups (N=50935 in each group). Results: After a mean follow up time of 3.08 years, the safety events occurred in 5014 patients in pitavastatin group (9.84%), 5542 in MIS group (10.88%), and 5343 in HIS group (10.49%). Multivariate Cox proportional hazards model showed that MIS and HIS statins were associated with a higher risk of safety events compared with pitavastatin (adjusted hazard ratio [aHR] 1.122, 95% confidence interval [CI] 1.08–1.17 for MIS and aHR 1.056, 95% CI 1.02–1.10 for HIS). Most events were NODM, with 4818 events in pitavastatin (9.46%), 5284 in MIS (10.37%), and 5113 in HIS group (10.04%). Multivariate Cox proportional hazard analysis showed higher risk of NODM in MIS (adjusted HR 1.111, 95% CI 1.07–1.16) and HIS (aHR 1.050, 95% CI 1.01–1.10) compared with pitavastatin. Time-varying HR analysis showed increased risk of NODM with use of all these statins for more than 1 year compared with non-statin users. Conclusions: Pitavastatin was associated with a lower risk of SAAEs, especially NODM, compared with atorvastatin and rosuvastatin. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Orient EuroPharma Co., Ltd.